Label-free assessment of differentiation efficiency in iPSC-derived spinal cord progenitor cells via Magnetic Resonance Relaxometry (MRR) - Tan, Jerome Zu Yao (2022)
The advent of induced pluripotent stem cells (iPSC) has provided a promising solution to the replacement of damaged neurons, especially in spinal cord injuries. Despite its merits, differentiation of iPSCs is a highly variable process, prompting the need to reliably assess the degree of differentiation across batches, and validate their quality. iPSC phenotypes are detected through labelling cells with fluorescent markers or immunofluorescence staining based methods, which perturb or destroy cells, preventing their further use. In this study, human iPSCs derived from Cord Lining Endothelial cells were differentiated into Spinal-cord Progenitor Cells (SCPCs) through a 10-day process. Label-free measurement of these cells were performed at different timepoints using Magnetic Resonance Relaxometry (MRR), a rapid and label-free technique to obtain critical cellular iron (Fe3+) content. MRR only requires <180k cells for measurements that takes up to 2 minutes without additional preparation. SCPCs have significantly different T2 relaxation times compared to iPSCs. Furthermore, SCPCs harvested at the end of the differentiation containing higher levels of residual pluripotent markers have lower T2 relaxation times when compared to SCPCs with lower levels of these markers. Our technology provides an efficient, label-free method to assess critical quality attributes of iPSCs and SCPCs.